2011
DOI: 10.1016/j.bmc.2011.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Directed evolution of a pyruvate aldolase to recognize a long chain acyl substrate

Abstract: The use of biological catalysts for industrial scale synthetic chemistry is highly attractive, given their cost effectiveness, high specificity that obviates the need for protecting group chemistry, and the environmentally benign nature of enzymatic procedures. Here we evolve the naturally occurring 2-keto-3-deoxy-6-phosphogluconate (KDPG) aldolases from Thermatoga maritima and Escherichia coli, into enzymes that recognize a non-functionalized electrophilic substrate, 2-keto-4-hydroxyoctonoate (KHO). Using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Protein directed evolution, on the other hand, offers the potential to improve the function of a specific enzyme (Cadwell and Joyce, 1992;Leung et al, 1989;Stemmer, 1994). Various techniques for directed evolution have been shown to be highly successful to improve or modify the function of the targeted enzyme (Cheriyan et al, 2011;Meyer et al, 2002;Zhao and Arnold, 1999) and by extension to improve the production of a desired product in a pathway (Atsumi and Liao, 2008;Christ et al, 2010;Wang and Liao, 2001). However, a major challenge in either bioprospecting or directed evolution is the effectiveness of the screening strategy, which determines the throughput of the effort.…”
Section: Introductionmentioning
confidence: 96%
“…Protein directed evolution, on the other hand, offers the potential to improve the function of a specific enzyme (Cadwell and Joyce, 1992;Leung et al, 1989;Stemmer, 1994). Various techniques for directed evolution have been shown to be highly successful to improve or modify the function of the targeted enzyme (Cheriyan et al, 2011;Meyer et al, 2002;Zhao and Arnold, 1999) and by extension to improve the production of a desired product in a pathway (Atsumi and Liao, 2008;Christ et al, 2010;Wang and Liao, 2001). However, a major challenge in either bioprospecting or directed evolution is the effectiveness of the screening strategy, which determines the throughput of the effort.…”
Section: Introductionmentioning
confidence: 96%
“…Previous data suggested that this selection method mainly identifies enhancements in substrate binding due, presumably, to the low in vivo concentration of the substrates. ( 15 ) To circumvent this issue, KDPG aldolase was fused to the signal sequence from the filamentous phage fd pIII gene which localizes the protein to the periplasm( 31 ) where the substrate concentration reflects the concentration in the medium. Using this method E. coli KDPG aldolase variants were selected for improved catalysis of two hydrophobic analogs of KDPG: (1) 2-keto-4-hydroxy-octonoate (KHO), a hydrophobic analog that lacks the C5 hydroxyl and C6 phosphate of KDPG; and (2) (4 S )-2-keto-4-hydroxy-4-(2′-pyridyl)butyrate ( S -KHPB), an analog containing a pyridyl group that is an important precursor for nikkomycin synthesis (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…( 15 ) Therefore random mutagenesis coupled to in vivo selection identified mutations that lowered the value of K M , but did not improve k cat . Albery and Knowles( 38 ) suggest that the first mutations in the evolution of a new activity often result in “uniform binding” where a mutation has a similar stabilizing effect on both the ground and transition states of the rate-limiting step, leaving the value of k cat unchanged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent engineering has used both directed evolution [21] and structure-based mutagenesis [20 •• ] to expand its substrate range to non-functionalized electrophilic substrates and pyridine carboxaldehyde substrates, respectively. Furthermore, the activity of the variant KDPGA with the pyridine carboxaldehyde substrate (4 S )-2-keto-4-hydroxy-4-(2′-pyridyl) butyrate ( S -KHPB) maintains high stereoselectivity at a similar rate to that of the wild-type enzyme with KDPG.…”
Section: Engineering Aldolases With Varied Substrate Specificitiesmentioning
confidence: 99%